Resilient Businesses for Sustainability Advances in Human Resource Management and Marketing, Part B. - Misra, Rajnish Kumar (Advanced Series in Management Series, 2024)
Today,there are many intricate disruptions originating from diverse sources, the 2nd volume provides invaluable insights into the role of Human Resource for sustainability and Marketing for building resilient businesses.Offering a comprehensive examination of how resilience is harnessed to build businesses capable of withstanding adversity